Los museos de la Ciencia y la Técnica, entre las musas y la modernidad - Vives, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
After a short miscellany about the evolution of Science Museums, a debate on the question "Must Science Museums be used for motivation or for learning?", is opened.